Collision dynamics and reactive uptake of OH radicals at liquid surfaces of atmospheric interest - Waring, C; King, K; Bagot, P; Costen, M; McKendrick, K (2011)
The inelastic scattering of OH radicals from the surfaces of a sequence of potentially reactive organic liquids: squalane (C30H62, 2,6,10,15,19,23-hexamethyltetracosane); squalene (C30H50, trans-2,6,10,15,19,23-hexamethyltetracosa-2,6,10,14,18,22-hexaene); and oleic acid (C18H34O2, cis-9-octadecanoic acid) was studied experimentally. A liquid long-chain perfluorinated polyether (PFPE, Krytox® 1506) was compared as a chemically inert reference. Gas-phase OH with an average laboratory-frame kinetic energy of 54 kJ mol-1 was generated by 355-nm photolysis of a low-pressure of HONO a short distance (9 mm) above the liquid surface. Scattered OH was detected at the same distance by laser-induced fluorescence (LIF). Appearance profiles as a function of photolysis-probe delay were recorded for selected OH v′ = 0, N′ rotational levels. The efficiency of momentum transfer to the surface is least for PFPE and highest for squalane, with squalene and oleic acid intermediate, but in all cases the speed distributions are markedly too hot to be consistent with a thermal accommodation mechanism. The rotational distribution is found to be a function of scattered OH speed. The generally high rotational temperatures implied by the relative fluxes for N′ = 1 and 5 were confirmed by LIF excitation spectra at the peak of the profile for each liquid. The trends in translational-to-rotational energy transfer were broadly consistent with the sequence in surface stiffness inferred from the translational inelasticity. The non-statistical distribution of OH fine-structure and Λ-doublet states produced by HONO photolysis appears to be effectively completely scrambled in collisions with the liquid surfaces. With due account taken of the product rotational distributions, and assuming that 100% of the OH scatters from PFPE, the integrated OH survival probabilities were: squalane (0.70 ± 0.08), squalene (0.61 ± 0.07) and oleic acid (0.76 ± 0.10). The 'missing' OH is presumed to have reacted at the liquid surface. Detailed comparison of the appearance profiles suggests that the main difference between squalane and squalene is loss of slower-moving OH, consistent with an additional capture mechanism at the vinyl sites. © 2011 the Owner Societies.